Provision of Soya in Coconut Water-Egg Yolk Diluent on Spermatozoon Quality of Simmental Bull at 4?C - Meliana, Sri; Hariani, Dyah (LenteraBio : Berkala Ilmiah Biologi, 2023)
The effect of storing a temperature of 4˚C resulting in cold shock has an impact on the quality of spermatozoon, it is necessary to add thinners as nutrients and extra-wide cryoprotectants with the addition of soy in the basic dilution od coconut water-egg yolk to maintain spermatozoon quality. The purpose od the study was to find out the effect of soy concentration in the basic dilution of coconut water 100 ml-10% egg yolk on the quality of Simmental cow spermatozoon. The study design using a Complete Randomizied Design consisted of 5 treatments: a basic dilution of coconut water 100 ml-10% egg yolk with soy concentration of 0g; 1,5g; 3g; 4,5g; and 6g with 4 repetitions. Simmental cow spermatozoon quality data including motility, viability and membrane integrity were analyzed using a one-way Anova. If the result are significant, followed by the Duncan test to find out the optimal soy concentration. The result showed that there was an effect of increasing the concentration of soya on the quality of simmental bull semen spermatozoon very significantly (P<0.00). Concentrations 4.5 g of soya showed a motility result of 58.13±0.39, viability of 59.60±2.84, and membrane integrity of 68.66±0.28 is optimal compared to other treatments. It was concluded that the addition of soya 4.5 g of soya is the optimal concentration in maintaining the quality of spermatozoon which is stored in a refrigerator temperature of 4-5˚C for 3 days and can be implemented in the field.